Comparison of green leafhopper (Nephotettix virescens) and zigzag leafhopper (Recilia dorsalis) population in paddy field at Merlimau, Melaka / Muhammad Hisyam Hashim - Hashim, Muhammad Hisyam (Faculty of Plantation and Agrotechnology, 2018)
Paddy is one of the major crops that are grown in most of the country in the world. The biggest challenge in planting paddy crop is the attack from the pest especially common insect pest that are found in paddy field which are Green Leafhopper (GLH) and Zigzag Leafhopper (ZLH). The study was conducted on a paddy area in Merlimau, Malacca for a duration of 5 weeks, which the data is collected twice a week. The aim of the study is to identify which insect pest is more severe between two major insect pests on paddy field which are GLH (Nephotettix virescens) and ZLH (Recilia dorsalis).Insect collection was done by using yellow sticky trap, with 3 replication for each collection. From the study, ZLH is more abundant compared to GLH as ZLH has the mean of 8.40 compared to 6.20 of GLH. The SPSS result also shows that the data collection between GLH and ZLH is non-significant to each other where (p>0.05). Some of the factor that contributes to the high collection of ZLH compared to GLH is the poor weed management and also less effective broadcast seeding procedure.